The problem of evil: skeptical theism leads to moral paralysis - Sehon, Scott Robert (International journal for philosophy of religion, 2010)
Natural disasters would seem to constitute evidence against the existence of God, for, on the face of things, it is mysterious why a completely good and all-powerful God would allow the sort of suffering we see from earthquakes, diseases, and the like. The skeptical theist replies that we should not expect to be able to understand God’s ways, and thus we should not regard it as surprising or mysterious that God would allow natural evil. I argue that skeptical theism leads to moral paralysis: accepting skeptical theism would undermine our ability to make any moral judgments whatsoever. Second, and more briefly, I argue that skeptical theism would undercut our ability to accept any form of the argument from design, including recent approaches based on fine-tuning.